Using the Nutri-Score to visualise food reformulation in Germany: the case of breakfast cereals - Corinna Gréa; Anna Dittmann; David Wolff; Hanna Haidar; Silvia Roser; Benedikt Merz; Stefan Storcksdieck genannt Bonsmann (BMC Public Health)
Abstract Background The reformulation of commonly consumed foods towards less sugar, fat, and salt is an important public health strategy to improve food choices of consumers and thus address the high prevalence of overweight and obesity. Front-of-pack nutrition labels like the Nutri-Score may drive reformulation and support nutritionally favourable food choices. Breakfast cereals are of special interest in that they tend to be high in sugar and are relatively often targeted at children. This study therefore aimed to evaluate the German breakfast cereal market in terms of reformulation efforts and to what extent these would show in a better Nutri-Score. Methods Using data from the German monitoring of packaged foods, changes in energy and nutrient content and the final nutritional score (FNS) of breakfast cereals, differentiated into children’s and non-children’s products, between 2019 (n = 888) and 2022 (n = 1473) were evaluated (Mann-Whitney test for two independent samples). Reformulation efforts were analysed in a subsample of paired products available in both years (n = 424). The Nutri-Score was calculated using the 2023 algorithm. Results Sugar content of children’s and non-children’s breakfast cereals decreased by 25.5% (p < 0.001) and 8.7% (p < 0.001), respectively, while fat content increased (+ 32.0% (p < 0.001) and + 7.0% (p < 0.036)). Especially for children’s breakfast cereals, the share of products with a ‘green’ (A or B) Nutri-Score was higher in 2022 than in 2019. At the same time, the share of less favourable breakfast cereals (Nutri-Score C-E) was higher for children’s than for non-children’s breakfast cereals in both years. For paired products, the FNS changed (positively or negatively) in 34.6% and concomitantly the Nutri-Score in 14.2% of cases. Products showing a better Nutri-Score were often reformulated in a way to just make it into the better class. Conclusion Improvements in nutrient content and FNS of breakfast cereals in Germany were mainly driven by shifts in the product portfolio, not by reformulation of existing products. Hence, any benefit for public health would require that consumers switch to (newly introduced) breakfast cereals with a more favourable composition. Overall, more reformulation efforts guided by a holistic product monitoring are needed to improve the nutritional quality of the food supply.